PENGARUH LATIHAN KNEE TUCK JUMP DENGAN STRETCHING DAN TANPA STRETCHING TERHADAP TINGGI JUMPING SMASH PADA ATLIT BULUTANGKIS DI KLATEN - WIDHINATA , ILHAM (2010)
and with quality. So that player can produce good achievement and maximal in every tournament. One of the component supporting is blow jumping smash that kneen and hard also the other components in concerned in game of badminton. For to support blow jumping smash that kneen and hard is needed power leg that strong to produce high vertical jump. Besides, power leg, in every practice to jumping smash is needed flexing and flexsibiltas good muscle. One of method to protect flixing muscle is with way of postpone muscle or strecthing. This reseach is representing research of shamp experience with research device nonequavalent depent variable. Excution of this research in the PB. Kusuma Klaten with 20 player sample (9-12 years). This sample is needed in two treatment, that first is knee tuck jump without streching, then to be continued with knee tuck jump with streching treatment. This research conducted as long 12 weeks that is month July until month September. Result analysis of early for normality data pre-test knee tuck jump with test Kolmogorov smirnov, with result of value P = 0,267. And result analysis of early for Homogenity data pre-test knee tuck jump, with result of value P=0,494. Then after treatments of knee tuck jump without stretching before and after, test influence of value P = 0,000. Knee tuck jump with stretching before and after, test influence of value P = 0,000. Difference post-test group of dept jump and knee tuck jump, test different influence of value P = 0,000 This research is showing that practice Pliometric knee tuck jump with stretching have value high vertical jump that more high (214,10cm) with compared practice pliometric knee tuck jump without stretching (208,15 cm) this matter that indicate usage stretching in practice pliometric knee tuck jump can improving high jumping smashing at player badminton